RPNCH: A method for constructing rooted phylogenetic networks from rooted triplets based on height function - Reyhani, Mohammad Hossein; Poormohammadi, Hadi (Archives of Advances in Biosciences, 2017)
Phylogenetic networks are a generalization of phylogenetic trees which permit the representation the non-tree-like events. It is NP-hard to construct an optimal rooted phylogenetic network from a given set of rooted triplets. This paper presents a novel algorithm called RPNCH. For a given set of rooted triplets, RPNCH tries to construct a rooted phylogenetic network with the minimum number of reticulation nodes that contains all the given rooted triplets. The performance of RPNCH algorithm on simulated data is reported here.